INFLUENCE OF ENTREPRENEURIAL KNOWLEDGE AND SELF-EFFICACY ON ENTREPRENEURIAL INTENTION: THE MEDIATING ROLE OF FAMILY ENVIRONMENT - Daniel Sebastian Styadinata; Lydiawati Soelaiman (International Journal of Application on Economics and Business, 2024)
Entrepreneurship is considered an effective solution to address employment issues and potential to stimulate economic growth. This research aims to investigate the influence of entrepreneurial knowledge and family environment on entrepreneurial intention among university students in West Jakarta, mediated by self-efficacy. The research methodology employed is descriptive quantitative, utilizing non-probability sampling and purposive sampling techniques. The sample consists of 196 students from West Jakarta universities. The results indicate that entrepreneurial knowledge has a positive and significant impact on entrepreneurial intention and students' self-efficacy. Meanwhile, the family environment does not directly affect entrepreneurial intention but has a significant influence on self-efficacy. Self-efficacy is proven to mediate the relationship between entrepreneurial knowledge and family environment with entrepreneurial intention. The contribution of this research is expected to increase the role of universities in providing theoretical and practical knowledge about entrepreneurship and the importance of support from the family environment to motivate entrepreneurship.